2020
DOI: 10.1111/jvim.15934
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic partial anomalous pulmonary venous connection in a kitten

Abstract: A 3-month-old intact female American Shorthair cat, with syncope and tachypnea, underwent cardiac examination which identified no heart murmur or gallop. Thoracic radiography disclosed mild generalized enlargement of the cardiac silhouette and a bronchial and interstitial pattern throughout the lungs. Echocardiography identified tubular structures near the left atrium. After agitated saline contrast imaging, persistent left cranial vena cava with unroofed coronary sinus was suspected. Computed tomography angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Most reported are heart murmur (often noted as right-sided systolic), jugular distension or pulsation and auscultatory abnormalities such as crackles and/or wheezes tachypnea, or evidence of thromboembolism. 30,31,35,38,93,94,96 There are few reports of laboratory findings in patients with PH. However, the authors would recommend a minimum database, including assessment for polycythemia, which could indicate right-to-left shunting or chronic hypoxia, heartworm antibody and antigen tests in endemic areas, fecal Baermann floatation for lungworm infections and, if possible, arterial blood gas analysis to assess for hypoxia (although obtaining this can be very difficult in a conscious cat, especially one with difficulty breathing – pulse oximetry might be considered as an alternative).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported are heart murmur (often noted as right-sided systolic), jugular distension or pulsation and auscultatory abnormalities such as crackles and/or wheezes tachypnea, or evidence of thromboembolism. 30,31,35,38,93,94,96 There are few reports of laboratory findings in patients with PH. However, the authors would recommend a minimum database, including assessment for polycythemia, which could indicate right-to-left shunting or chronic hypoxia, heartworm antibody and antigen tests in endemic areas, fecal Baermann floatation for lungworm infections and, if possible, arterial blood gas analysis to assess for hypoxia (although obtaining this can be very difficult in a conscious cat, especially one with difficulty breathing – pulse oximetry might be considered as an alternative).…”
Section: Diagnosismentioning
confidence: 99%
“…30,32,35 Radiographs can demonstrate a variety of abnormalities, including cardiomegaly, pulmonary infiltrates, blunting, tortuosity or enlargement of the pulmonary arteries, or of both the pulmonary arteries and veins, and hepatomegaly. 27,30,38…”
Section: Diagnosismentioning
confidence: 99%
“…A retrospective study that reviewed 290 dogs with cardiovascular malformations from 1953 to 1965 revealed that only 1 case was diagnosed PAPVC with secundum atrial septal defect [40]. For the published case reports, there are only 3 dogs [41][42][43] and each 1 of chicken [44] and foal [45] that are diagnosed as TAPVC; only 4 dogs [46][47][48] and 2 cats [49,50] are PAPVC. One canine case reported in 1975 did not describe its detail (TAPVC or PAPVC) [51].…”
Section: Anomalous Pulmonary Venous Connectionmentioning
confidence: 99%
“…For obtaining the full picture of abnormal development of pulmonary veins, multidetector computed tomography and magnetic resonance imaging both can provide good images. The importance of advanced imaging modules in diagnosing these complex cardiovascular developmental diseases had been emphasized in these years [49,50]. Both of multidetector computed tomography and magnetic resonance imaging are non-invasive, and they can offer multiplanar and three-dimensional reconstructive model.…”
Section: Anomalous Pulmonary Venous Connectionmentioning
confidence: 99%
See 1 more Smart Citation